A educação alimentar e nutricional nos anos iniciais do Ensino Fundamental da rede pública municipal de Rio Verde-GO - CABRAL, Hellen Cristina de Oliveira (2008)
This study was carried out within the research line Culture and Educational Processes, and its object of study was the food and nutritional education of children in municipal primary schools. Its aims were to verify the children s nutritional status and to evaluate their eating habits; to verify the presence of themes such as eating and nutrition in the school curriculum; to analyze the National Curricular Parameters as far as eating and nutrition are concerned, and establish criteria to evaluate textbooks and analyze food and nutritional education supplementary material available for teachers and used in the school. The research was carried out in three schools from Rio Verde-GO, with children from farms, from the outskirts of town and downtown. The eating and nutritional conditions of children between 6 and 10 years old were investigated, as well as eating habits, type of food consumed, acceptance of school food, etc. The choice for these aspects took into account the Brazilian reality presented in several studies, which revealed a tendency to obesity in children of this age, regardless of social class. We also studied how teachers have dealt with the eating and nutrition theme with their students, the available material for this work besides the textbook and its appropriateness and connection to what the National Curricular Parameters establish. The results showed that, according to the WHO (2007) BMI, 1,7% had a low BMI for their age, 67,8% were eutrophic, 19,1% were overweight and 11,4% were obese. 30,5% of the children examined were above adequate weight. A significant number of children have had inadequate eating habits, consuming food such as pastry, pasta, sweets, etc. Regarding the teacher s work they had difficulty in approaching the theme, especially in the first and second grades. Thus, the school staff needs more guidance about correct eating habits, since this theme is only dealt with, in the first and second grades, during the Food Week, while in the third, fourth and fifth grades it is approached during the whole school period. In fact, the theme is the school Food